PENGUKURAN INTENSITAS RADIASI YANG DIPANCARKAN OLEH HANDPHONE DAN PENGARUHNYA TERHADAP KESEHATAN - -, Hartina; -, Iswadi; L, Muh Said (Fakultas Sains dan Teknologi UIN ALauddin, 2014)
The research was conducted by taking a sample of 25 pieces of cell phone. Mobile radiation intensity measured electromagnetic waves are receiving phone calls. Measurements were made by placing two headphone in a different room with a range of Â± 20 meters. Tool used to measure the intensity of radiation of electromagnetic waves emitted by mobile phone radiation is a measure C32-QX5. Values were collected before phone calls and performed on two conditions after receiving the phone call is a normal condition and the condition of the loudspeaker. The purpose of this study was to determine the intensity of the electromagnetic radiation emitted by mobile phones with different brands and types and determine their effects on health.Results showed that all cell phones that have measured the intensity of the radiation was still safe to use because it has an average radiation intensity 6 mW/cm2, which limits the intensity of radiation that can be tolerated by the body is equal to 10 mW/cm2. The use of mobile phones continuously for one hour a day in the ten-year timeframe, estimated the value of the intensity of radiation received by the body tissue will exceed safe limits.Key words: Intensity Radiation, Measures Radiation, Mobile phone and Health Risk